PENGARUH JOB INSECURITY TERHADAP TURNOVER INTENTION DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT ADIENT AUTOMOTIVE INDONESIA - Rodiatul Aulla; Ali Jufri; Puspa Dewi Yulianty (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the impact of job insecurity on turnover intention with work engagement as a mediating variable among employees of PT Adient Automotive Indonesia. The study identifies the direct relationship between job insecurity and turnover intention, as well as the impact of job insecurity on work engagement. The results indicate that job insecurity has a positive and significant impact on turnover intention and a negative and significant impact on work engagement. Moreover, work engagement acts as a mediating variable that strengthens the effect of job insecurity on turnover intention. Using a quantitative approach and multiple regression analysis, this study provides empirical evidence that high job insecurity can increase the intention to leave the company, especially among employees with low levels of work engagement. Therefore, companies need to focus on efforts to enhance work engagement in order to mitigate the negative impact of job insecurity and prevent high turnover.